Clinicopathological Significance of STAT3 and p-STAT3 among 91 Patients with Adenocarcinoma of the Esophagogastric Junction. (3rd October 2022) - Ma, Rui-Jie; Zheng, Qi-Ming; Zhang, Nan; Sun, Zhi-Gang
Abstract : Adenocarcinoma of the esophagogastric junction (AEG) has increased rapidly worldwide during the last few decades. The purpose of this study is to investigate the clinical and prognostic characteristics of signal transduction and activator of transcription factor 3(STAT3) and phosphorylated STAT3 (p-STAT3) expression in AEG patients. We retrospectively analyzed the immunohistochemical results of 61 AEG patients and followed up for 5 years, while Western blot was performed on tissues from another 30 AEG patients. The results showed that STAT3 and p-STAT3 were overexpressed in AEG tissues (P < 0.05, P < 0.01 ). The high expression of STAT3 was significantly associated with the pTNM stage (P < 0.05 ), and the increased expression of p-STAT3 was significantly associated with depth of invasion (pT), lymph node metastasis (pN), and pTNM stage (P < 0.05, P < 0.05, P < 0.05 ). The 5-year survival rate for AEG patients was 41.0% and was significantly associated with tumor differentiation, pN, pTNM, and p-STAT3 (P < 0.05, P < 0.01, P < 0.05, P < 0.01 ). Cox regression analysis confirmed that tumor differentiation, pN, and high expression of p-STAT3 were independent risk factors for the 5-year survival rate in patients with AEG (P < 0.05, P < 0.01, P < 0.05 ). Our study showed that STAT3 and p-STAT3 play a critical role in AEG development.